Needs Analysis and Teachers’ Perceptions: A Study of English Undergraduate Students - Abdul Qadar (University of Chitral Journal of Linguistics and Literature, 2019)
Needs Analysis in the context of language-learning-teaching is an importantprocess to design a certain course and syllabus. It helps course designers to setobjectives, choose content, method of instruction, appropriate teaching aids andclassroom activities for different courses. This paper reports the perceptions of theresearchers on the English language learning needs of the English undergraduatestudents of Shaheed Benazir Bhutto University Sheringal, Pakistan. The data isbased on the researchers’ personal experience and a first-hand observation of thepopulation as the researchers have been teaching in the target context for about adecade. Furthermore, the researchers have always been in discussion with theirstudents and colleagues about the target students’ English leaning needs, preferredlearning styles, motivation in learning English, interest, strengths/weaknesses, andattitude toward English learning in the target setting. Learners’ assignments, examanswer sheets, and presentations have also been used is a source of data collection.A needs analysis model proposed by Hutchinson and Waters (1987) has beenapplied in order to analyze the data. The results show that the students lack wellgrammatical sentences, have poor spellings, capitalization problems, limitedvocabulary, unaware of collocations, poor/slow reading comprehension, and lackof effective presentation skills. Furthermore, most of the students have lack ofinvolvement in classroom activities and feel shy in speaking English language. Itwas reported that provision of authentic material, interesting activities, suitableaudio-visual aids, relevant texts, language labs and other logistic arrangements canbetter help them in learning English language. The findings demonstrate that thestudents wished to have a learner-centered-course which helps them excel in theiracademic life and learning English language.